A method for preparing nanodiamond based on graphene vertical sheets

By growing a graphene upright sheet layer containing transition metal atoms on a quartz sheet and annealing in a low-pressure oxygen-containing environment, the problems of reduced nanodiamond performance and difficult to control grain size in the prior art are solved, and a method for preparing nanodiamonds with uniform size and good dispersion are realized.

CN116752114BActive Publication Date: 2025-02-28ZHEJIANG UNIV OF TECH

Patent Information

Application Number
CN202310639800.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-02-28
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

In existing methods for preparing nanodiamonds, nitrogen elements in explosives may be introduced into nanodiamonds, resulting in reduced performance and difficult to control grain size.

Method used

The graphene vertical sheet containing transition metal atoms was grown on the quartz sheet by hot wire chemical vapor deposition (HFCVD) method, and annealed in a low-pressure oxygen-containing environment to promote the transformation of the graphene vertical sheet into a nanodiamond structure with uniform size and good dispersion.

Benefits of technology

It has achieved the conversion of graphene vertical sheet into nanodiamond under low pressure conditions, which has mild conditions and low cost. At the same time, the process is simple and the equipment requirements are low, which has important scientific significance and value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004261278420000011
    Figure HDA0004261278420000011
  • Figure HDA0004261278420000012
    Figure HDA0004261278420000012
  • Figure HDA0004261278420000021
    Figure HDA0004261278420000021
Patent Text Reader

Abstract

The present invention discloses a method for preparing nano-diamonds based on graphene vertical sheets. The present invention utilizes a hot wire chemical vapor deposition system to grow graphene vertical sheets containing tantalum atoms, and transforms the graphene vertical sheets into nano-diamonds under relatively low pressure conditions. The method has the characteristics of mild conditions and low cost. The method has low requirements on equipment, simple process and easy operation. The method has important scientific significance and value for developing a new method for preparing nano-diamonds.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a new method for preparing nano-diamond based on graphene vertical sheets. Background Art

[0002] Nanodiamond is a diamond with nanometer particle size, which determines that it has other special properties different from macro diamond, such as nanometer size effect, large specific surface area, low Debye temperature, high chemical activity, etc. These unique physical, chemical and mechanical properties make it play an important role in polishing and lubrication, electronic devices and biomedicine.

[0003] At present, there are many methods for preparing nanodiamonds, such as detonation method, chemical vapor deposition (CVD) method, laser ablation method, etc. Among them, the detonation method is currently the cheapest and most efficient method for preparing nanodiamond powder. Most of the nanodiamonds used in business and industry are produced by this method. The detonation method uses the instantaneous ultra-high temperature and high pressure generated by the explosion of negative oxygen balance explosives to rearrange the free carbon atoms released by the explosives and aggregate and crystallize to form nanodiamonds. However, during the preparation process of this method, the nitrogen element in the explosive will be introduced into the nanodiamond, and the grains are prone to agglomeration during the detonation, which reduces its performance as a nanopowder. Therefore, it is of great value to develop new methods for preparing nanodiamonds.

[0004] Under the action of transition metal atoms, graphite can be transformed into a diamond structure under lower pressure (see patent ZL.202210305804.7 for details). The size of the diamond grains obtained by this method is related to the size of the graphite grains before the phase change. Due to the complex microstructure of graphite and the different grain sizes, the grain size of the nanodiamonds obtained after the phase change is also difficult to control. Graphene vertical sheets are a structure composed of graphene sheets arranged perpendicular to the substrate. The thickness of the sheet is generally around 10nm. At the same time, this structure has a large specific surface area, and the surface can adsorb more transition metal atoms, and the metal atoms will be more evenly distributed. This means that graphene vertical sheets have a higher probability of phase change, and it is easier to obtain nanodiamonds of uniform size. Therefore, it is a good precursor for realizing the low-pressure conversion of graphite into nanodiamonds. Therefore, we used the hot filament chemical vapor deposition (HFCVD) method to grow vertical graphene sheets containing transition metal atoms on a quartz wafer, and then annealed the vertical graphene sheets in a low-pressure oxygen-containing environment to promote their transformation into nanodiamond structures with uniform size and good dispersion. Summary of the invention

[0005] The present invention develops a new method for preparing nano-diamonds based on graphene vertical sheets. The method anneals the graphene vertical sheets containing transition metal atoms in an oxygen-containing environment to achieve the transformation of the graphene sheets into nano-diamonds.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] A method for preparing nanodiamond based on graphene vertical sheets, the method comprising the following steps:

[0008] (1) Tantalum wire carbonization:

[0009] In a hot wire chemical vapor deposition device equipped with a tantalum wire, pure hydrogen and acetone A are used as carbonization gas sources to carbonize the tantalum wire, the flow rate of the pure hydrogen is 150-200 sccm, and the acetone A is introduced into the reaction chamber by hydrogen bubbling at a flow rate of 50-80 sccm. The procedure for carbonizing the tantalum wire is as follows: controlling the carbonization gas pressure to be 5.3-6 kPa, carbonizing at 5-7 V for 5-10 min, carbonizing at 10-12 V for 5-10 min, and carbonizing at 13-15 V for 2-5 min. After carbonization is completed, the introduction of acetone is stopped, and the voltage is rapidly reduced to 0 in a hydrogen atmosphere to obtain a carbonized tantalum wire;

[0010] (2) Hot-wire chemical vapor deposition growth of tantalum-containing graphene vertical sheets

[0011] The cleaned quartz substrate is placed in the hot wire chemical vapor deposition equipment described in step (1), and the carbonized tantalum wire described in step (1) is used as the heating wire; acetone B is used as the carbon source, and the acetone B is bubbled into the reaction chamber with hydrogen at a flow rate of 80 to 120 sccm, the growth power is 1600 to 1800 W, the growth pressure is 0.6-1.5 kPa (preferably 1.0 kPa), and the growth time is 5 to 30 min; after the growth is completed, the gas is stopped, and the power is reduced to 0 at a rate of 0.5-2 V / min (preferably 1 V / min) to obtain tantalum-containing graphene vertical sheets;

[0012] (3) Oxygen atmosphere sealed tube annealing

[0013] The tantalum-containing graphene sheet described in step (2) is placed in a quartz sealing system, and the air pressure in the quartz tube is controlled to be 100-500 Pa (preferably 100 Pa) when the tube is sealed, and the gas in the tube is an oxygen-containing gas; the quartz tube is placed in a muffle furnace and kept at 800-1000° C. for 30-60 min, and cooled to room temperature to obtain a diamond structure on the upright graphene sheet.

[0014] The letters of acetone A and acetone B in the present invention are only for distinguishing acetone at different stages for the convenience of description and have no other special meanings.

[0015] The carbonization of the tantalum wire in step (1) has two functions: inhibiting the escape of tantalum atoms during the growth process and controlling the escape rate; and extending the service life of the tantalum wire. In one embodiment of the present invention, the procedure for carbonizing the tantalum wire is as follows: the flow rate of the pure hydrogen is 200 sccm, the acetone A is introduced into the reaction chamber by bubbling hydrogen at a flow rate of 80 sccm, the carbonization gas pressure is controlled to be 5.7 kPa, 7V carbonization for 10 minutes, 12V carbonization for 10 minutes, and 15V carbonization for 5 minutes. Those skilled in the art should know that within the voltage and carbonization time range limited by the present invention, a comparable effect can be achieved.

[0016] During the growth of graphene in step (2), tantalum atoms will escape from the surface of the hot tantalum wire at high temperature and deposit into the sample.

[0017] Further, the cleaned quartz substrate in step (2) is obtained as follows:

[0018] A double-sided polished quartz sheet with a size of 12×12×1 mm was ultrasonically cleaned in acetone and ethanol for 10 to 20 minutes in sequence, rinsed with deionized water, and dried with nitrogen to obtain the cleaned quartz substrate.

[0019] In one embodiment of the present invention, the acetone B in step (2) is brought into the reaction chamber by bubbling hydrogen at a flow rate of 100 sccm, the growth power is 1800 W, the growth pressure is 1.0 kPa, and the growth time is 30 min; after the growth is completed, the gas is stopped and the power is reduced to 0 at a rate of 1 V / min.

[0020] The purpose of annealing in an oxygen-containing atmosphere in step (3) is to chemically adsorb oxygen atoms on the surface of the graphene vertical sheet sample, thereby promoting the transformation of graphene into a diamond structure under the combined action of surface oxygen atoms and tantalum atoms.

[0021] The present invention particularly recommends that the oxygen-containing gas in step (3) is air; further, the mass ratio of oxygen contained in the oxygen-containing gas to the tantalum-containing graphene sheet is 1:20-100; in one embodiment of the present invention, the volume of the quartz tube is 15-20 mL.

[0022] The present invention particularly recommends that the gas pressure in the quartz tube be controlled to be 100 Pa when sealing the tube in step (3), the insulation temperature be 1000° C., and the time be 30 min.

[0023] The present invention particularly recommends a method for preparing nanodiamonds based on graphene vertical sheets, the method comprising the following steps:

[0024] (1) Tantalum wire carbonization:

[0025] In a hot wire chemical vapor deposition device equipped with a tantalum wire, pure hydrogen and acetone A are used as carbonization gas sources to carbonize the tantalum wire, the flow rate of the pure hydrogen is 200 sccm, and the acetone A is introduced into the reaction chamber by hydrogen bubbling with a flow rate of 80 sccm. The procedure for carbonizing the tantalum wire is as follows: controlling the carbonization gas pressure to be 5.7 kPa, carbonizing at 7V for 10 minutes, carbonizing at 12V for 10 minutes, and carbonizing at 15V for 5 minutes. After the carbonization is completed, the introduction of acetone is stopped, and the voltage is rapidly reduced to 0 in a hydrogen atmosphere to obtain a carbonized tantalum wire;

[0026] (2) Hot-wire chemical vapor deposition growth of tantalum-containing graphene vertical sheets

[0027] The cleaned quartz substrate is placed in the hot wire chemical vapor deposition equipment described in step (1), and the carbonized tantalum wire described in step (1) is used as the heating wire; acetone B is used as the carbon source, and the acetone B is bubbled into the reaction chamber with hydrogen at a flow rate of 100 sccm, the growth power is 1800 W, the growth pressure is 1.0 kPa, and the growth time is 30 min; after the growth is completed, the gas is stopped, and the power is reduced to 0 at a rate of 1 V / min to obtain tantalum-containing graphene vertical sheets;

[0028] (3) Oxygen atmosphere sealed tube annealing

[0029] The tantalum-containing graphene sheet described in step (2) is placed in a quartz sealing system, and the air pressure in the quartz tube is controlled to be 100 Pa when the tube is sealed, and the gas in the tube is oxygen-containing gas; the quartz tube is placed in a muffle furnace and kept at 1000° C. for 30 minutes, and cooled to room temperature to obtain a diamond structure on the upright graphene sheet.

[0030] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in: 1. Utilizing a hot wire chemical vapor deposition system to grow vertical graphene sheets containing tantalum atoms, the vertical graphene sheets are transformed into nanodiamonds under relatively low pressure conditions, which has the characteristics of mild conditions and low cost; 2. This method has low equipment requirements, simple process and easy operation; 3. It has important scientific significance and value for the development of new nanodiamond preparation methods. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM image of the vertical graphene sheets grown by HFCVD;

[0032] Figure 2 This is the TEM-EDS image of the vertical graphene sheets grown by HFCVD;

[0033] Figure 3 is the SEM image of sample 1 after annealing under 100 Pa pressure;

[0034] Figure 4This is the energy spectrum (TEM-EDS) of sample 1 after annealing under 100Pa pressure;

[0035] Figure 5 TEM image of sample 1 after annealing under 100 Pa pressure;

[0036] Figure 6 is the SEM image of sample 2 after annealing under 500Pa pressure;

[0037] Figure 7 This is the TEM-EDS image of sample 2 after annealing under 500Pa pressure;

[0038] Figure 8 TEM image of sample 2 after annealing under 500Pa pressure;

[0039] Fig. 9 is the SEM image of sample 3 after annealing under 10Pa pressure;

[0040] Fig.10 This is the TEM-EDS image of sample 3 after annealing under 10Pa pressure;

[0041] Fig.11 TEM image of sample 3 after annealing under 10Pa pressure;

[0042] Fig.12 is the SEM image of sample 4 after annealing under 1000Pa pressure;

[0043] Fig.13 TEM-EDS diagram of sample 4 after annealing under 1000Pa pressure;

[0044] Fig.14 TEM image of sample 4 after annealing under 1000Pa pressure;

[0045] Fig.15 is the SEM image of sample 5 after vacuum (pressure <1Pa) annealing;

[0046] Fig.16 This is the energy spectrum (TEM-EDS) image of sample 5 after vacuum (pressure <1Pa) annealing;

[0047] Fig.17 TEM image of sample 5 after vacuum (pressure <1Pa) annealing; DETAILED DESCRIPTION

[0048] The present invention is further described below by means of specific embodiments, but the protection scope of the present invention is not limited thereto.

[0049] In the following examples, the quartz sheet was prepared by Zhongnuo New Materials (Beijing) Technology Co., Ltd., and the quartz sheet substrate material size was a double-sided polished quartz sheet of 12×12×1 mm;

[0050] The hot-wire chemical vapor deposition equipment was purchased from Shanghai Jiaoyou Diamond Coating Company, model JUHFCVD001;

[0051] The ultrasonic cleaning instrument is manufactured by Kunshan Ultrasonic Instrument Co., Ltd. and its model is KQ5200DE.

[0052] Example 1

[0053] (1) The quartz plate is placed in acetone and ethanol in turn, ultrasonically cleaned (140W ultrasonic for 15 min), cleaned with deionized water, and dried (dried with a nitrogen gun) to obtain a pretreated quartz plate; the above pretreatment is to obtain a quartz plate with a clean surface. After drying, it is wrapped with lens cleaning paper and set aside for use.

[0054] (2) In the hot wire chemical vapor deposition (HFCVD) equipment, the tantalum wire is installed 12 mm away from the sample surface. The carbonization gas sources are hydrogen and acetone. The acetone is brought into the reaction chamber by bubbling with hydrogen. The flow rate of pure hydrogen is 200 sccm, and the flow rate of acetone is 80 sccm. The carbonization is carried out at 7 V for 10 min, 12 V for 10 min, and 15 V for 5 min. The total carbonization time is 25 min. The carbonization pressure is controlled to be 5.7 kPa. After the carbonization is completed, the power is quickly reduced to 0 in the hydrogen atmosphere to complete the tantalum wire carbonization process.

[0055] (3) The quartz wafer pretreated in step (1) is placed as a substrate in the hot wire chemical vapor deposition (HFCVD) device treated in step (2), and acetone is introduced. The acetone flow rate is 100 sccm, the power is 1800 W, and the gas pressure is controlled at 1.0 kPa. After 30 minutes, all gases are turned off and the power is reduced to 0 at a rate of 1 V / min to complete the growth of graphite vertical sheets on the quartz wafer.

[0056] (4) Place the sample treated in step (3) into a quartz tube and seal the tube. When sealing the tube, control the pressure in the tube to be 100 Pa (the gas in the tube is air) and the gas volume to be 17 ml. Heat the muffle furnace to 1000° C. in advance, place the sealed quartz tube (with the sample inside), and keep it at 1000° C. for 30 minutes. After the insulation time is over, take out the sample immediately and cool it at room temperature to complete the annealing process.

[0057] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0058] Figure 1This is a SEM image of HFCVD grown graphene vertical lamellae (obtained in step (2)). The vertical lamellae structure on the surface is fully distributed, and the lamellae thickness is distributed in the range of about 10 nm.

[0059] Figure 2 This is the energy spectrum (TEM-EDS) of the HFCVD grown graphene vertical sheets (obtained in step (2)). The untreated graphene vertical sheets mainly contain three elements: C, O, and Ta. The Cu element in the energy spectrum comes from the transmission copper mesh during sample preparation, and a small amount of O element comes from the oxygen generated by the decomposition of acetone during the sample growth process.

[0060] Figure 3 This is the SEM picture of sample 1, compared with Figure 1 The untreated graphene upright flakes show no obvious surface changes in sample 1 after oxidation annealing.

[0061] Figure 4 This is the TEM-EDS diagram of sample 1. Figure 2 It can be seen that this area has relatively high O content and Ta content.

[0062] Figure 5 This is the TEM image of sample 1 after the experiment. In the high-magnification image, a large number of small particles with a diameter of 2 to 4 nm can be observed. By magnifying and analyzing these small particles, three crystal plane spacings of 0.221 to 0.219 nm, 0.215 to 0.206 nm, and 0.193 nm can be obtained, corresponding to three different crystal planes of hexagonal diamond (100), diamond (111) or hexagonal diamond (002), and hexagonal diamond (101). The measured angles between the diamond (111) planes are 70.7°, 71.5°, and 71.6°, the angle between the hexagonal diamond (100) plane and the hexagonal diamond (002) plane is 89.6°, and the angle between the hexagonal diamond (100) plane and the hexagonal diamond (101) plane is 61.9°, which are basically close to the three standard diamond angles of 70.5°, 90°, and 63.8°. Therefore, the four framed areas in Figure (b) are all diffraction information of diamond, and the diamond size is below 5nm. This is consistent with theoretical calculation studies showing that Ta promotes the transformation of graphite into diamond.

[0063] Example 2

[0064] (1) The quartz plate is placed in acetone and ethanol in turn, ultrasonically cleaned (140W ultrasound for 15 min), cleaned with deionized water, and dried (dried with a nitrogen gun) to obtain a pre-treated surface-cleaned quartz plate. After drying, it is wrapped with lens-cleaning paper for standby use.

[0065] (2) In the hot wire chemical vapor deposition (HFCVD) equipment, the tantalum wire is installed 12 mm away from the sample surface. The carbonization gas sources are hydrogen and acetone. The acetone is brought into the reaction chamber by bubbling with hydrogen. The flow rate of pure hydrogen is 200 sccm, and the flow rate of acetone is 80 sccm. The carbonization is carried out at 7 V for 10 min, 12 V for 10 min, and 15 V for 5 min. The total carbonization time is 25 min. The carbonization pressure is controlled to be 5.7 kPa. After the carbonization is completed, the power is quickly reduced to 0 in the hydrogen atmosphere to complete the tantalum wire carbonization process.

[0066] (3) The quartz wafer pretreated in step (1) is placed as a substrate in the hot wire chemical vapor deposition (HFCVD) device treated in step (2), and acetone is introduced. The acetone flow rate is 100 sccm, the power is 1800 W, and the gas pressure is controlled at 1.0 kPa. After 30 minutes, all gases are turned off and the power is reduced to 0 at a rate of 1 V / min to complete the growth of graphite vertical sheets on the quartz wafer.

[0067] (4) Place the sample treated in step (3) into a quartz tube and seal the tube. When sealing the tube, control the pressure in the tube to 500 Pa (the gas in the tube is air) and the gas volume to 17 ml. Heat the muffle furnace to 1000° C. in advance, place the sealed quartz tube (with the sample inside) and keep it warm for 30 minutes. After the insulation time is over, take out the sample immediately and cool it at room temperature to complete the annealing process.

[0068] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0069] Figure 6 This is the SEM picture of sample 2. Figure 1 The untreated graphene has upright lamellae, the surface lamellae structure of sample 2 is more distorted, and some small lamellae appear.

[0070] Figure 7 This is the TEM-EDS diagram of sample 2. Since there are many graphite ring structures in the transmission sample, it has a higher C content than sample 1. Figure 2 The energy spectrum of the untreated graphene upright sheets still shows that this area still has relatively high O and Ta contents.

[0071] Figure 8This is the TEM image of sample 2 after the experiment. In the high-magnification image, some small particles with a diameter of 2 to 4 nm can be observed. By magnifying and analyzing these small particles, two crystal plane spacings of 0.214 to 0.208 nm and 0.178 nm can be obtained, corresponding to the diamond (111) plane and (200) plane, respectively. The angle between the diamond (111) plane and the diamond (111) plane and (200) plane is measured to be 71.8°, and the angle between the diamond (111) plane and the (200) plane is 53.6°, which is basically close to the standard diamond angles of 70.5° and 54.7°. Therefore, the two boxed areas in Figure (b) are the diffraction information of diamond.

[0072] Example 3 (Comparative Example)

[0073] (1) Place the quartz plate in acetone and ethanol in turn, ultrasonically clean it (140W ultrasound for 15 minutes), rinse it with deionized water, and dry it (blow it dry with a nitrogen gun) to obtain a pre-treated clean quartz plate. After drying, wrap it with lens cleaning paper for later use.

[0074] (2) The tantalum wire was installed 12 mm away from the sample surface. The carbonization gas sources were hydrogen and acetone. Acetone was introduced into the reaction chamber by bubbling with hydrogen. The flow rate of pure hydrogen was 200 sccm, and the flow rate of acetone was 80 sccm. Carbonization was performed at 7 V for 10 min, 12 V for 10 min, and 15 V for 5 min. The total carbonization time was 25 min. The carbonization pressure was controlled to be 5.7 kPa. After the carbonization was completed, the power was quickly reduced to 0 in the hydrogen atmosphere to complete the tantalum wire carbonization process.

[0075] (3) The quartz wafer pretreated in step (1) is placed as a substrate in the hot wire chemical vapor deposition (HFCVD) device treated in step (2), and acetone is introduced. The acetone flow rate is 100 sccm, the power is 1800 W, and the gas pressure is controlled at 1.0 kPa. After 30 minutes, all gases are turned off and the power is reduced to 0 at a rate of 1 V / min to complete the growth of graphite vertical sheets on the quartz wafer.

[0076] (4) Place the sample treated in step (3) into a quartz tube and seal the tube. When sealing the tube, control the pressure in the tube to be 10 Pa (the gas in the tube is air) and the gas volume to be 17 ml. Heat the muffle furnace to 1000° C. in advance, place the sealed quartz tube (with the sample inside) and keep it warm for 30 minutes. After the insulation time is over, take out the sample immediately and cool it at room temperature to complete the annealing process.

[0077] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0078] Fig. 9 is the SEM image of sample 3, and Figure 1Compared with the untreated graphene upright flakes, the surface flake structure of sample 3 did not change significantly.

[0079] Fig.10 This is the TEM-EDS diagram of sample 3. Figure 2 It can be seen that the element composition and content of the sample are basically the same as those of the untreated sample.

[0080] Fig.11 This is the TEM image of sample 3. No diamond structure was observed in this sample, indicating that annealing at a lower oxygen content does not promote the phase transition of graphite to diamond structure.

[0081] Example 4 (Comparative Example)

[0082] (1) Place the quartz plate in acetone and ethanol in turn, ultrasonically clean it (140W ultrasound for 15 minutes), rinse it with deionized water, and dry it (blow it dry with a nitrogen gun) to obtain a pre-treated clean quartz plate. After drying, wrap it with lens cleaning paper for later use.

[0083] (2) The tantalum wire was installed 12 mm away from the sample surface. The carbonization gas sources were hydrogen and acetone. Acetone was introduced into the reaction chamber by bubbling with hydrogen. The flow rate of pure hydrogen was 200 sccm, and the flow rate of acetone was 80 sccm. Carbonization was performed at 7 V for 10 min, 12 V for 10 min, and 15 V for 5 min. The total carbonization time was 25 min. The carbonization pressure was controlled to be 5.7 kPa. After the carbonization was completed, the power was quickly reduced to 0 in the hydrogen atmosphere to complete the tantalum wire carbonization process.

[0084] (3) The quartz wafer pretreated in step (1) is placed as a substrate in the hot wire chemical vapor deposition (HFCVD) device treated in step (2), and acetone is introduced. The acetone flow rate is 100 sccm, the power is 1800 W, and the gas pressure is controlled at 1.0 kPa. After 30 minutes, all gases are turned off and the power is reduced to 0 at a rate of 1 V / min to complete the growth of graphite vertical sheets on the quartz wafer.

[0085] (4) Place the sample treated in step (3) into a quartz tube and seal the tube. When sealing the tube, control the pressure in the tube to be 1000 Pa (the gas in the tube is air) and the gas volume to be 17 ml. Heat the muffle furnace to 1000° C. in advance and place the sealed quartz tube (with the sample inside) in a heat preservation process for 30 min. After the heat preservation time is over, take out the sample immediately and cool it at room temperature to complete the annealing process.

[0086] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0087] Fig.12This is the SEM picture of sample 4. Figure 1 The untreated graphene has upright lamellae, and the lamellae structure on the surface of sample 4 has increased significantly and become more twisted.

[0088] Fig.13 This is the TEM-EDS diagram of sample 4. Figure 2 It can be seen that the sample has a higher O content.

[0089] Fig.14 The TEM image of sample 4 shows spike-like structures and small patch structures in (a), where the spike-like structures are graphite bands composed of the (002) crystal plane of graphite, and the high-magnification image of the small patch structure is shown in (b). No obvious stripe structure is observed in the high-magnification image. Combined with the high oxygen content of the sample, it is believed that the graphite structure here has been oxidized to an amorphous phase. No diamond structure was observed in this sample, indicating that too high an oxygen content is not conducive to the transformation of graphite into diamond.

[0090] Example 5 (Comparative Example)

[0091] (1) Place the quartz plate in acetone and ethanol in turn, ultrasonically clean it (140W ultrasound for 15 minutes), rinse it with deionized water, and dry it (blow it dry with a nitrogen gun) to obtain a pre-treated clean quartz plate. After drying, wrap it with lens cleaning paper for later use.

[0092] (2) The tantalum wire was installed 12 mm away from the sample surface. The carbonization gas sources were hydrogen and acetone. Acetone was introduced into the reaction chamber by bubbling with hydrogen. The flow rate of pure hydrogen was 200 sccm, and the flow rate of acetone was 80 sccm. Carbonization was performed at 7 V for 10 min, 12 V for 10 min, and 15 V for 5 min. The total carbonization time was 25 min. The carbonization pressure was controlled to be 5.7 kPa. After the carbonization was completed, the power was quickly reduced to 0 in the hydrogen atmosphere to complete the tantalum wire carbonization process.

[0093] (3) The quartz wafer pretreated in step (1) is placed as a substrate in the hot wire chemical vapor deposition (HFCVD) device treated in step (2), and acetone is introduced. The acetone flow rate is 100 sccm, the power is 1800 W, and the gas pressure is controlled at 1.0 kPa. After 30 minutes, all gases are turned off and the power is reduced to 0 at a rate of 1 V / min to complete the growth of graphite vertical sheets on the quartz wafer.

[0094] (4) Place the sample treated in step (3) into a quartz tube and seal the tube. When sealing the tube, control the tube to be evacuated to a vacuum (air pressure <1Pa, the gas in the tube is air), the gas volume is 17ml, and the muffle furnace is heated to 1000°C in advance, and place the sealed quartz tube (with the sample inside) and keep it warm for 30 minutes. After the insulation time is over, take out the sample immediately and cool it at room temperature to complete the annealing process.

[0095] Field emission scanning electron microscopy (FESEM) and high resolution transmission electron microscopy (HRTEM) were used to observe the composition of the samples after the experiment.

[0096] Fig.15 This is the SEM picture of sample 5. Figure 1 The untreated graphene has upright flakes, and the volume of the single flake structure on the surface of sample 5 increases and the wrinkles decrease.

[0097] Fig.16 This is the TEM-EDS diagram of sample 5, which shows a very low oxygen content.

[0098] Fig.17 This is the TEM image of sample 5. In Figure (a), a ring can be observed, where the ring-shaped structure is a graphite ring composed of the (002) crystal plane of graphite. Its high-magnification image is shown in Figure (b). No diamond structure was observed in this sample, indicating that vacuum annealing does not promote the transformation of tantalum-containing graphite into diamond.

Claims

1. A method for preparing nanodiamonds based on graphene vertical sheets, characterized in that The method comprises the following steps: (1) Tantalum wire carbonization: In a hot wire chemical vapor deposition device equipped with a tantalum wire, pure hydrogen and acetone A are used as carbonization gas sources to carbonize the tantalum wire, the flow rate of the pure hydrogen is 150-200 sccm, and the acetone A is brought into the reaction chamber by hydrogen bubbling at a flow rate of 50-80 sccm. The procedure for carbonizing the tantalum wire is as follows: controlling the carbonization gas pressure to be 5.3-6 kPa, carbonizing at 5-7 V for 5-10 min, carbonizing at 10-12 V for 5-10 min, and carbonizing at 13-15 V for 2-5 min. After the carbonization is completed, the introduction of acetone is stopped, and the voltage is rapidly reduced to 0 in a hydrogen atmosphere to obtain a carbonized tantalum wire; the acetone A and acetone B are both acetone, and the letters are only used to distinguish acetone at different stages; (2) Hot-wire chemical vapor deposition growth of tantalum-containing graphene vertical sheets The cleaned quartz substrate is placed in the hot wire chemical vapor deposition equipment described in step (1), and the carbonized tantalum wire described in step (1) is used as the heating wire; acetone B is used as the carbon source, and the acetone B is introduced into the reaction chamber by bubbling hydrogen at a flow rate of 80-120 sccm, the growth power is 1600-1800 W, the growth pressure is 0.6-1.5 kPa, and the growth time is 5-30 min; after the growth is completed, the gas is stopped, and the power is reduced to 0 at a rate of 0.5-2 V / min to obtain tantalum-containing graphene vertical sheets; (3) Oxygen atmosphere sealed tube annealing The tantalum-containing graphene sheet described in step (2) is placed in a quartz sealing system, and the air pressure in the quartz tube is controlled to be 100-500 Pa when the tube is sealed, and the gas in the tube is an oxygen-containing gas; the quartz tube is placed in a muffle furnace and kept at 800-1000° C. for 30-60 minutes, and cooled to room temperature to obtain a diamond structure on the upright graphene sheet.

2. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The procedure for carbonizing the tantalum wire in step (1) is as follows: the flow rate of the pure hydrogen is 200 sccm, the acetone A is brought into the reaction chamber by bubbling hydrogen at a flow rate of 80 sccm, the carbonization gas pressure is controlled to be 5.7 kPa, carbonization is performed at 7 V for 10 min, carbonization is performed at 12 V for 10 min, and carbonization is performed at 15 V for 5 min.

3. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The cleaned quartz substrate in step (2) is obtained as follows: A double-sided polished quartz sheet with a size of 12×12×1 mm was ultrasonically cleaned in acetone and ethanol for 10 to 20 minutes in sequence, rinsed with deionized water, and dried with nitrogen to obtain the cleaned quartz substrate.

4. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: In step (2), the acetone B is introduced into the reaction chamber by bubbling hydrogen at a flow rate of 100 sccm, the growth power is 1800 W, the growth pressure is 1.0 kPa, and the growth time is 30 min. After the growth is completed, the gas is stopped and the power is reduced to 0 at a rate of 1 V / min.

5. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The oxygen-containing gas in step (3) is air.

6. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The mass ratio of the oxygen contained in the oxygen-containing gas in step (3) to the tantalum-containing graphene sheet is 1:20-100.

7. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The volume of the quartz tube in step (3) is 15-20 mL.

8. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: In step (3), the air pressure in the quartz tube is controlled to be 100 Pa when the tube is sealed.

9. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The insulation temperature in step (3) is 1000° C. and the insulation time is 30 minutes.

10. The method for preparing nanodiamonds based on graphene vertical sheets according to claim 1, characterized in that: The method comprises the following steps: (1) Tantalum wire carbonization: In a hot wire chemical vapor deposition device equipped with a tantalum wire, pure hydrogen and acetone A are used as carbonization gas sources to carbonize the tantalum wire, the flow rate of the pure hydrogen is 200 sccm, and the acetone A is introduced into the reaction chamber by hydrogen bubbling with a flow rate of 80 sccm. The procedure for carbonizing the tantalum wire is as follows: controlling the carbonization gas pressure to be 5.7 kPa, carbonizing at 7V for 10 minutes, carbonizing at 12V for 10 minutes, and carbonizing at 15V for 5 minutes. After the carbonization is completed, the introduction of acetone is stopped, and the voltage is rapidly reduced to 0 in a hydrogen atmosphere to obtain a carbonized tantalum wire; (2) Hot-wire chemical vapor deposition growth of tantalum-containing graphene vertical sheets The cleaned quartz substrate is placed in the hot wire chemical vapor deposition equipment described in step (1), and the carbonized tantalum wire described in step (1) is used as the heating wire; acetone B is used as the carbon source, and the acetone B is bubbled into the reaction chamber with hydrogen at a flow rate of 100 sccm, the growth power is 1800 W, the growth pressure is 1.0 kPa, and the growth time is 30 min; after the growth is completed, the gas is stopped, and the power is reduced to 0 at a rate of 1 V / min to obtain tantalum-containing graphene vertical sheets; (3) Oxygen atmosphere sealed tube annealing The tantalum-containing graphene sheet described in step (2) is placed in a quartz sealing system, and the air pressure in the quartz tube is controlled to be 100 Pa when the tube is sealed, and the gas in the tube is oxygen-containing gas; the quartz tube is placed in a muffle furnace and kept at 1000° C. for 30 minutes, and cooled to room temperature to obtain a diamond structure on the upright graphene sheet.

Citation Information

Patent Citations

  • Nanometer diamond-graphene nanobelt composite film and preparation method thereof

    CN104894526A

  • Method for converting graphite phase in nano-diamond film into diamond phase under low pressure

    CN114752916A

Cited By

  • Method for preparing diamond based on graphite under normal pressure

    CN118062842A

  • A method for preparing diamond based on graphite under normal pressure

    CN118062842B